2014
DOI: 10.1055/s-0034-1372628
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Ischemic Preconditioning is Detrimental to Anaerobic Performance in Cyclists

Abstract: We verified the acute effect of ischemic preconditioning (IPC) in cyclists before high-intensity and short-duration activity. 15 amateur cyclists participated in a random crossover model on 2 different days [IPC or CONTROL (CON)]. Ischemic preconditioning consisted of 4 cycles of 5 min occlusion/5 min reperfusion in each thigh. After IPC or CON, volunteers performed a series of Wingate tests to evaluate anaerobic performance (maximal [Pmax] and medium [Pmed] power output, total anaerobic power, and fatigue ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 14 publications
5
40
2
4
Order By: Relevance
“…Evidence supporting this hypothesis was provided in a recent meta-analysis (Salvador et al 2016). If so, this helps explain why exercise performances reliant on anaerobic processes are not improved with IPC when shorter times of 5-16 min are employed (Crisafulli et al 2011;Gibson et al 2013;Paixão et al 2014;Gibson et al 2015;Lalonde and Curnier 2015) compared to longer periods (present study, Jean-St-Michel et al 2011;Patterson et al 2015). Other factors may also contribute for the heterogeneity in the effect between studies, as participant characteristics (e.g., sex, training status) and study methods (e.g., exercise mode, pre-study restrictions, IPC protocol) differ widely (Incognito et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence supporting this hypothesis was provided in a recent meta-analysis (Salvador et al 2016). If so, this helps explain why exercise performances reliant on anaerobic processes are not improved with IPC when shorter times of 5-16 min are employed (Crisafulli et al 2011;Gibson et al 2013;Paixão et al 2014;Gibson et al 2015;Lalonde and Curnier 2015) compared to longer periods (present study, Jean-St-Michel et al 2011;Patterson et al 2015). Other factors may also contribute for the heterogeneity in the effect between studies, as participant characteristics (e.g., sex, training status) and study methods (e.g., exercise mode, pre-study restrictions, IPC protocol) differ widely (Incognito et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There were no cases of deep vein thrombosis or injury to the preconditioned limb, and no protocol was prematurely terminated due to subject discomfort. During the control condition, participants followed an identical protocol, but instead, the cuff was inflated only to 20 mm Hg (Bailey et al 2012;Paixão et al 2014;Cruz et al 2015). The time between the end of the procedure and the start of the performance test was 33 min (Salvador et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, enhanced exercise performance has been found when muscle IP was applied before various kinds of effort such as handgrip, cycling, running, and swimming (8,9,24,27,41,44,59). Although some authors found uncertain or no effect (13,34,36,67), or even a negative effect (56), of IP on exercise performance, the majority of the reported research suggests that IP induces some mild improvements in the capacity to exercise. However, the mechanisms through which IP positively influences exercise remain largely speculative, and several hypotheses have been formulated about the putative effects of IP on exercise performance.…”
mentioning
confidence: 99%
“…The occlusion and reperfusion phases were conducted alternately between the thighs, with subjects remaining in supine rest position. The SHAM intervention was identical to IPC interventions but with an absolute pressure of 20 mm Hg during the "occlusion phases" 21 . During the inflation and deflation phases of the IPC and SHAM, the blood flow was constantly checked by auscultation of the tibial anterior artery to confirmed occlusion/reperfusion phases properly 18 .…”
Section: Ischemic Preconditioningmentioning
confidence: 99%